A KINETIC STUDY OF MERANTI SAWDUST (SHOREA SPP) PYROLYSIS USING THERMOGRAVIMETRIC ANALYSIS - Fitria, Fitria; Subagyono, RR Dirgarini Julia Nurlianti; Gunawan, Rahmat (PROSIDING SEMINAR KIMIA, 2023)
A kinetic study of pyrolysis of meranti wood using the Kissinger-Akahira-Sunose (KAS), Ozawa-Flynn-Wall (OFW), and Friedman methods using thermogravimetric analysis has been carried out. This study aims to study the synergistic effect of meranti wood and determine the activation energy value. Pyrolysis was carried out at four heating rates, namely 10, 15, 20, and 25°C/minute under N2 gas. The temperature range in the active pyrolysis of meranti wood is 128,42-521°C. The average activation energy values of pyrolysis of meranti wood using the KAS, OFW, and Friedman methods were 170,84 ± 30,07 kJ/mol, 180,36 ± 29,42 kJ/mol, respectively 174, ± 54,77 kJ/mol. Keywords: meranti wood, kinetics studies, pyrolysis, thermogravimetric analysis